Pengaruh Kemudahan Penggunaan, Kemanfaatan Dan Risiko Terhadap Minat Menggunakan E-Wallet Pada Generasi Milenial Kota Batam - Putri, Silvia Yalni; Ompusunggu, Hermaya (Peneliti.net, 2023)
Making non-cash payments during the digital era is growing along with technological developments, especially information, which is now increasingly sophisticated. The sophistication of today's technology will certainly have a good impact, especially on payment transaction systems in electronic form or often also called e-wallets. The use of e-wallets is expected to help the payment system to be more efficient and make it easier for users to do digital transactions. In addition to the use of e-wallets, the author uses primary data by distributing questionnaires using a Likert scale to obtain processed data. This writing provides a separate assessment or criteria for the object to be studied (purposive sampling) where the method is included in non-probability sampling. The population in this study were active students in the accounting study program in Batam City who were using or had made digital transactions using e-wallets, while the sample consisted of 100 respondents who were analyzed using the slovin formula. From the research activities carried out by the authors on the data, it shows that there is a positive and significant influence among all the variables used, namely ease of use, benefits, and risks to interest in using e-wallets.